Harmonization of the Implementation of Restorative Justice in Indonesia in a Gender Perspective: A Normative Empirical Assessment of Legal Consistency and Effectiveness - Mashendra (MUWAZAH : jurnal kajian gender, 2025)
This study analyzes the harmonization of the implementation of restorative justice in Indonesia through a comparative normative empirical approach involving five countries, namely New Zealand, Australia, Canada, South Africa, and Indonesia. The type of research used is normative-empirical legal research with legislative, conceptual, comparative law, and sociological legal approaches. Normative analysis of restorative justice regulations is combined with empirical data to assess legal consistency, institutional capacity, and integration of socio-cultural values in practice. Data collection was carried out through document studies of laws and regulations, institutional policies, and scientific literature, as well as in-depth interviews with law enforcement officials, restorative justice facilitators, and community leaders. The validity of the data is maintained through triangulation of sources and methods. Data analysis was carried out qualitatively using content analysis, comparative analysis between countries, and the Miles and Huberman interactive analysis model which includes data reduction, data presentation, and conclusion drawn. The results show that New Zealand has the highest level of effectiveness through a comprehensively integrated legislative framework, while Indonesia still faces sectoral regulatory fragmentation with limited implementation beyond children's cases. Comparisons show Indonesia scores lowest in system integration and institutional support, despite having strong potential in community-based mediation practices and customary values. The main challenges include weak legal harmonization and limitations in monitoring and evaluation systems. This study contributes to the development of a contextual and sustainable model of restorative justice implementation in a pluralistic legal system.